Good Corporate Governance in moderating Intellectual Capital and Voluntary Reporting on Company Performance - Aviani Widyastuti; Ahmad Waluya Jati; Wardatul Jannah (Jurnal ASET (Akuntansi Riset), 2023)
Abstract Main Purpose - This study aims to examine and analyze the relationship between Intellectual Capital and Voluntary Reporting on company performance moderated by good corporate governanceMethod - The approach in this study is a quantitative approach using explanatory research. Research data were analyzed using multiple linear regression and MRA with the study population, namely manufacturing companies listed on the IDX in 2020 and 2021Main Findings - Intellectual Capital, Voluntary Reporting, and Good corporate governance are important instruments to provide an overview of the company's condition to investors, thereby attracting interest to invest in companies that affect the capital that the company will obtain to increase company profits. Companies that are managed with good operational management can increase the value of their company's performance. One that can increase the value of the company is by managing the resources owned by the company and presenting this information to stakeholders.Theory and Practical Implications - The results of this study provide empirical evidence that company performance increases when the value of intellectual capital increases. Therefore, the higher the intellectual capital in the company, the greater the value of the company's performance. Intellectual capital can be a strategic resource for companies in creating and increasing company profits obtained from investors' investment returns, thus being able to improve company performance.Novelty - The development in this study is the existence of a moderating variable of good corporate governance, where in previous research it was explained that good corporate governance is one of the key factors in a company because of both asset structure, financial structure, and policies and strategic steps that were decided to address pressure from the company's external condition is determined by the components of good corporate governance.